Climatic niche and the potential effect of future climate changes on the distribution of Araucaria Angustifolia (Bert.) O. Kuntze in South America Nicho climático e o potencial efeito das mudanças climáticas futuras sobre a distribuição de Araucaria Angustifolia (Bert.) O. Kuntze na América do Sul - de Aguiar J.T.* (2017)
© 2017.The objective of this study was to evaluate the climatic climate and a response of Araucária angustifolia (Bert.) O. Kuntze to future climatic changes due to bioclimatic variables. Using data from geographic coordinates extracted from SpeciesLink database and explanatory bioclimatic variables from WorldClim, the data were analyzed in the R sofwtare. The results obtained showed a decrease of 30.87% in 2070 of areas potentially favorable for the development of this species.